WEB-BASED STUDENT ADMINISTRATION INFORMATION SYSTEM IN TSANAWIYAH NEGERI 2 SEMARANG MADRASAH - Zaenal Mustofa; Wahyu Efendy Yusuf; Maya Utami Dewi (Journal of Engineering, Electrical and Informatics, 2021)
The problem of repetitive work carried out by homeroom teachers when processing grades at school is the main problem experienced by every homeroom teacher at school. A good academic system is needed because it is able to minimize the work of the homeroom teacher. MTs Negeri 2 Semarang in processing value data reporting still uses the conventional method, namely by filling in the value leger. The teaching teacher fills the value data into the grade leger according to each subject. Then the homeroom teacher reported in the form of grades per subject. Then from the value data per subject the homeroom teacher must reprocess it into grades per student and print it. This will be a repetitive task if the homeroom teacher also serves as a teaching teacher. The report still uses copy and paste from flash to flash which has a very high risk of losing data. This is coupled with the school building which is divided into two buildings with a considerable distance between the old building and the new building which makes teaching teachers feel reluctant to report grades. To solve the existing problems, the authors propose a web-based value data administration system at MTs Negeri 2 Semarang which will make it easier for teachers to process and report value data. The program is expected to be able to deal with existing problems and ease the work of the homeroom teacher.